Estimating efficiencies in irrigation projects - Lee, Teang Shui; Ali, Md. Hazrat; Kwok, Chee Yan; Eloubaidy, Aziz F.; Foong, K. C. (Universiti Putra Malaysia, 1999)
Surface irrigation systems are designed and operated to supply the individual irrigation requirements in each field while controlling deep percolation, runoff, evapotranspiration, and operational losses. The performance of a farm irrigation system is evaluated by the efficiency with which water is diverted, conveyed, applied and by the adequacy and uniformity of application in each field on the farm. The objective of this paper is to determine the conveyance efficiency, water-use efficiency, and water distribution efficiency to get the overall Muda project efficiency. The nonlinear Muski-ngum-Cunge method (Cunge, 1969) was applied to calculate the conveyance losses from the Pedu dam to the end of the main canal, a total reaches of about 108 km. The mean conveyance efficiency from the Pedu Dam to the Pelubang Barrage was found to be 66.5 %, and the same from the Pedu Dam to the end of the Central & Northern canals was found to be 59%. The estimated conveyance efficiency was not compared because no such study had been done or if any, is not available. Since no cross-sectional data is available for the lateral canals, the MADA’s calculated lateral conveyance efficiency of 80% was considered throughout the Muda area. Using CCRBD A1 block data as reported by Batumalai and Nassir (1986), the distribution efficiency was found to be 93.79%. The water use efficiency was estimated using MADA’s field water supply data. The overall project efficiency for the main-season and off-season, were found to be 17.89% and 32.29%, respectively.